Metagenomics reveals the effect of long-term fertilization on carbon cycle in the maize rhizosphere - Li, Yanan; Wang, Chengyu; Chang, Hongyan; Zhang, Yumang; Liu, Shuxia; He, Wentian (Frontiers in Microbiology, 2023)
Long-term fertilization can result in the changes in carbon (C) cycle in the maize rhizosphere soil. However, there have been few reports on the impacts of microbial regulatory mechanisms on the C cycle in soil. In the study, we analyzed the response of functional genes that regulate the C fixation, decomposition and methane (CH4) metabolism in maize rhizosphere soil to different fertilization treatments using metagenomics analysis. As the dominant C fixation pathway in maize rhizosphere soil, the abundance of the functional genes regulating the reductive citrate cycle (rTCA cycle) including korA, korB and IHD1was higher under the chemical nitrogen (N) fertilizer treatments (N, NPK, NPKS) than maize straw return treatments (S, PKS). The NPK treatment decreased the abundance of functional genes involved in 3-HP cycle (porA, porB and porD), which was one of the major C fixation pathways in soil aside from dicarboxylate-hydroxybutyrate (DC/4-HB cycle) and Calvin cycle. The abundance of functional genes related to C degradation was higher in S, PKS and NPKS treatments than N and NPK treatments, and chemical N fertilizer application had a significant effect on C degradation. The dominant Methanaogenesis pathway in maize rhizosphere soil, used acetate as a substrate, and was significantly promoted under chemical N fertilizer application. The functional genes that were related to CH4 oxidation (i.e., pmoA and pmoB) were reduced under N and NPK treatments. Moreover, soil chemical properties had a significant impact on the functional genes related to C fixation and degradation, with SOC and NO3- -N being the main regulators. These results implied that N fertilization rather than maize straw return had a greater influence on the C cycle in maize rhizosphere soil.